Variable coordination of carbazolyl-bis(tetrazole) ligands in lanthanide chemistry12. Issue 43 (18th October 2018) - Gajecki, Leah; Berg, David J.; Hoenisch, Josh; Oliver, Allen G.
Abstract : Lanthanide complexes of 1, 8-bis(2′-isopropyltetrazo-5′-yl)-3, 6-di- tert -butylcarbazolide adopt geometries that include planar, buckled and tetrazolyl-bridged tridentate, as well as bidentate, bonding modes. Abstract : The synthesis of the protioligand 1, 8-bis(2′-isopropyltetrazo-5′-yl)-3, 6-di- tert -butylcarbazole, HCzT iPr 2, is described. The acid–base reaction of2 with various Ln[N(SiMe3 )2 ]3 (Ln = Ce, Sm, Er, Yb, Y) precursors leads to products displaying a variety of different bonding modes for the CzT iPr− ligand as revealed by X-ray crystallographic studies. The smaller lanthanides form Ln(CzT iPr )[N(SiMe3 )2 ]2 complexes (Ln = Er (3 ), Yb(4 )) with a near planar, tridentate coordination mode for the CzT iPr− ligand. In contrast, the larger lanthanides form Ln(CzT iPr )2 [N(SiMe3 )2 ] complexes (Ln = Ce (5 ), Sm (6 )) at room temperature that feature a sandwich structure with a highly distorted tridentate mode where tetrazole canting allows the metal to sit well out of the carbazole plane. Attempts to force additional CzT iPr− ligands onto Er or Yb at elevated temperature results in isolation of trace siloxide complexes Ln(CzT iPr )2 (OSiMe3 ) (Ln = Er (3a ), Yb (4a )) that adopt a flat tridentate ligand bonding mode similar to3 and4 . Surprisingly, the high temperature reaction of2 with Y[N(SiMe3 )2 ]3 affords Y(CzT iPr )3, 7, featuring two tridentate and one bidentate CzT iPr ligands. Partial hydrolysis of6 occurs over time to produce a hydroxo-bridged dimer that also features one bridging and one bidentate CzT iPr ligand, Sm(κ 3 -CzT iPr )(κ 3 -μ-CzT iPr )(μ-OH)2 Sm(κ 3 -CzT iPr )(κ 2 -CzT iPr ), 6a, further illustrating the remarkable coordinative flexibility of the CzT iPr ligand system.